Competition before sunset: The case of the Finnish ATM market - Maria Kopsakangas-Savolainen; Tuomas Takalo (Bank of Finland, 2012)
We build a simple model to study service fee competition between an incumbent and an independent ATM deployer, and its optimal regulation. We use the model to analyze an actual regulation of such a market by competition authorities in Finland. We find that socially optimal first-best fees would imply negative profits for the independent deployer, calling for a Ramsey regulation. While the Finnish regulation pushes the foreign fee downwards towards its socially optimal level, the regulated fees are likely to remain too high from the welfare point of view. In contrast with the actual regulation, it would be essential to regulate the independent deployer's interchange fee, as the incumbent deployer internalizes the effect of its foreign fee on consumer usage of the rival's network and has little incentive for foreclosure.
URN:NBN:fi:bof-20140807187
Keywords: 330